2022
DOI: 10.3389/fcell.2022.828282
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogens, the Vinyl Ether-Linked Glycerophospholipids, Enhance Learning and Memory by Regulating Brain-Derived Neurotrophic Factor

Abstract: Plasmalogens (Pls), a kind of glycerophospholipids, have shown potent biological effects but their role in hippocampus-dependent memory remained mostly elusive. Here, we first report Pls can enhance endogenous expression of brain-derived neurotrophic factor (Bdnf) in the hippocampus and promotes neurogenesis associated with improvement of learning and memory in mice. Genomic and proteomic studies revealed that Pls enhanced recruitment of CREB transcription factor onto the murine Bdnf promoter region via upregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…However, the present study did not find a significant change in urinary 8-OHdG, known to reflect oxidative stress ( Valavanidis et al, 2009 ; Urbaniak et al, 2020 ). Moreover, no statistically significant change was observed in blood BDNF although plasmalogens are assumed to improve brain function by increasing BDNF ( Hossain et al, 2022 ). These results suggest that neither urinary 8-OHdG nor blood BDNF may reflect a minute change in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present study did not find a significant change in urinary 8-OHdG, known to reflect oxidative stress ( Valavanidis et al, 2009 ; Urbaniak et al, 2020 ). Moreover, no statistically significant change was observed in blood BDNF although plasmalogens are assumed to improve brain function by increasing BDNF ( Hossain et al, 2022 ). These results suggest that neither urinary 8-OHdG nor blood BDNF may reflect a minute change in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a simple method was developed to extract a large number of plasmalogens from animals ( Mawatari et al, 2007 ; Mawatari et al, 2009 ), which enabled research on plasmalogen treatment. In mice, plasmalogen administration not only suppressed inflammation-induced activation of microglia, amyloid formation, and neuronal cell death in the brain but also improved cognitive function ( Ifuku et al, 2012 ; Katafuchi et al, 2012 ; Hossain et al, 2013 ; Hossain et al, 2018 ; Gu et al, 2022 ; Hossain et al, 2022 ). A randomized controlled trial demonstrated that scallop-derived purified plasmalogens improved cognitive function in patients with mild AD or mild cognitive impairment ( Fujino et al, 2017 ; Fujino et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental data have shown that curcumin-loaded lipid nanoparticles may promote BDNF expression and that the ω-3 PUFA content of the nanoparticles may be beneficial for enhancing BDNF activity [159,186]. In recent years, lipid-based therapies have been suggested as an alternative strategy for slowing neurodegeneration and inhibiting neuroinflammation [187][188][189]. PUFA-chain ethanolamine plasmalogens have been described as bioactive lipids and can be 100-fold more powerful in stimulating neurorepair than conventional ω-3 PUFA species [187].…”
Section: Nanoscale Assemblies Of Bioactive Lipids Offering Therapeuti...mentioning
confidence: 99%
“…PUFA-chain ethanolamine plasmalogens have been described as bioactive lipids and can be 100-fold more powerful in stimulating neurorepair than conventional ω-3 PUFA species [187]. By analyzing the results from clinical and in vitro experiments, it has been concluded that certain plasmalogen lipid derivatives may enhance neurotrophic BDNF signaling and thus promote neurogenesis [189].…”
Section: Nanoscale Assemblies Of Bioactive Lipids Offering Therapeuti...mentioning
confidence: 99%
See 1 more Smart Citation